Mitigating risks of disease transmission in the wild meat food chain from forest to fork in Cameroon - CIFOR-ICRAF (CIFOR-ICRAF, 2022)
Many wild species are widely hunted and provide important food, nutritional and financial benefits to many communities in the tropics. However, the potential pathogen spillover from wildlife to humans is a risk that has received increased attention since the outbreak of the COVID-19 pandemic. Wild animals used for food are major reservoirs for a number of foodborne pathogens such as Salmonella or Giardia but also viruses (e.g. Ebola, Marburg and others) transmitted from animal body fluids. Many zoonotic diseases also pose risks of epidemics and pandemics. Despite the potential dangers associated with wildlife use, there are practical ways of reducing the risk of contagion at different points in the wild meat food chain.